2004
DOI: 10.1136/jmg.2003.017483
|View full text |Cite
|
Sign up to set email alerts
|

Somatic NKX2-5 mutations as a novel mechanism of disease in complex congenital heart disease

Abstract: NKX2-5 is a pivotal transcription factor in heart development. Previous studies on lymphocytic DNA provided evidence of familial NKX2-5 gene mutations in cardiac malformations. Common mutations are rare in unrelated families. We analysed, by direct sequencing, the gene encoding NKX2-5 in the diseased heart tissues of 68 patients with complex congenital heart disease, focussing particularly on atrial, ventricular, and atrioventricular septal defects. We identified 35 non-synonymous NKX2-5 mutations in the disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(90 citation statements)
references
References 20 publications
2
86
1
1
Order By: Relevance
“…Somatic mutations can not be detected by genetic analysis of lymphocytic DNA alone, and mosaicism may reduce the likelihood of detection in the affected tissue. Therefore, mutations in cardiac tissues may be absent or sporadic in blood lymphocytes of the same person (40). In the present study, 2 novel heterozygous mutations of GATA6 (p.G367X and p.G394C) were identified in the malformed heart tissues of 2 out of 52 patients with TOF.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Somatic mutations can not be detected by genetic analysis of lymphocytic DNA alone, and mosaicism may reduce the likelihood of detection in the affected tissue. Therefore, mutations in cardiac tissues may be absent or sporadic in blood lymphocytes of the same person (40). In the present study, 2 novel heterozygous mutations of GATA6 (p.G367X and p.G394C) were identified in the malformed heart tissues of 2 out of 52 patients with TOF.…”
Section: Discussionmentioning
confidence: 81%
“…Somatic mutations have been identified Somatic mutations in the GATA6 gene underlie sporadic tetralogy of Fallot in GATA4 and its molecular partners, NKX2-5 and TBX5, as well as the transcription factor HAND1 and HEY2 in cardiac tissue derived from hearts with CHD (40)(41)(42)(43)(44)(45)(46)(47)(48). GATA6 is another member of the GATA family, and its expression and function overlap at least partially with those of GATA4, NKX2-5 and TBX5 during cardiovascular genesis, which makes it logical to hypothesize that somatic GATA6 mutations are involved in the pathogenesis of TOF.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to these findings, the figure of 3/53 mutations (approximately 6%) in our patient cohort with positive family history suggests that the NKX2-5 mutations could be a major cause of familial CHD. Notably, the remarkable genetic heterogeneity of CHD was proven by an inability to detect mutations in nearly 99% of our cohort patients, despite somatic NKX2-5 mutations being a likely mechanism of CHD in some patients (Reamon-Buettner and Borlak, 2004). Hence, the contribution of genes other than NKX2-5 to CHD pathogenesis seems probable.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, many studies have demonstrated that somatic mutations play crucial role in congenital heart diseases (56,57). Reamon-Buettner et al (56) have found somatic NKX2-5 sequence variants by direct sequencing in >95% of human hearts (n=68) with septal defects.…”
Section: Discussionmentioning
confidence: 99%